Tafsir Alegoris, Konstruksi Teologis, dan Unsur Erotis dalam Kitab Kidung Agung - Agetta Putri Awijaya (Asosiasi Teolog Indonesia, 2016)
Song of Songs is afforded relatively rare attention in church, where an allegorical mode of reading often continues to serve as the default interpretative strategy for examining this particular book of the Bible. And this remains the case, despite the development of numerous other approaches that can better account for elements of eroticism as contained in that book. In this essay, discursive problematics arising from the interpretation of Song of Songs are considered in detail, in order to ascertain the reason for the church's aversion toward using some such exegetical method that would be more attuned to the erotic elements within Song of Songs. One's own willingness to be open to such erotic elements in Song of Songs may even assist in bringing the church to realize the riches to be found therein. Such riches may then also serve as basis for a more progressive constructive theology concerning human sexuality. As such, the church may thus regard Song of Songs as its biblical warrant for constructing a theology that regards sexuality in a more positive manner.